Physiological Response of Cape Gooseberry Plants to Fusarium oxysporum f. sp. physali, Fusaric Acid, and Water Deficit in a Hydrophonic System - Mendoza-Vargas, Luis Alberto; Villamarín-Romero, Wendy Paola; Cotrino-Tierradentro, Anderson Steven; Ramírez-Gil, Joaquín Guillermo; Chávez-Arias, Cristhian Camilo; Restrepo-Díaz, Hermann; Gómez-Caro, Sandra (Frontiers in Plant Science, 2021)
Cape gooseberry production has been limited by vascular wilt caused by Fusarium oxysporum f. sp. physali (Foph). Fusaric acid (FA) is a mycotoxin produced by many Fusarium species including F. oxysporum formae speciales. The effects of the interaction between this mycotoxin and plants (such as cape gooseberry) under biotic stress (water deficit (WD)) have been little explored. Three experiments were carried out. The objectives of this study were to evaluate (i) different Foph inoculum densities (1 x 104 and 1 x 106 conidia mL-1; experiment 1); (ii) the effect of times of exposure (0, 6, 9, and 12 h) and FA concentrations (0, 12.5, 25, 50, and 100 mg L-1; experiment 2), and (iii) the interaction between Foph (1 x 104 conidia mL-1) or FA (25 mg L-1 x 9 h) and WD conditions (experiment 3) on the physiological (plant growth, leaf stomatal conductance (gs), and photochemical efficiency of PSII (Fv/Fm ratio)) and biochemical (malondialdehyde (MDA) and proline) responses of cape gooseberry seedlings ecotype Colombia. First experiment showed that Foph inoculum density of 1 x 106 conidia mL-1 caused the highest incidence of the disease (100%). In the second experiment, gs (~40.6 mmol m-2 s-1) and Fv/Fm ratio (~0.59) decreased, whereas MDA (~9.8 µmol g-1 FW) increased in plants under exposure times of 9 and 12 h and a FA concentration of 100 mg L-1 compared to plants without FA exposure or concentrations (169.8 mmol m-2 s-1, 0.8, and 7.2 µmol g-1 FW for gs, Fv/Fm ratio and MDA, respectively). In the last experiment, the interaction between Foph or FA and WD promoted a higher area under the disease progress curve (AUDPC) (Foph × WD = 44.5 and FA × WD = 37) and lower gs (Foph × WD = 6.2 mmol m-2 s-1 and FA × WD = 9.5 mmol m-2 s-1) compared to plants without any interaction. This research could be considered a new approach for the rapid scanning of responses to the effects of FA, Foph, and WD stress not only on cape gooseberry plants but also on other species from the Solanaceae family.